2006
DOI: 10.1108/00346650610676794
|View full text |Cite
|
Sign up to set email alerts
|

A study into the antimicrobial effects of cloves (Syzgium aromaticum) and cinnamon (Cinnamomum zeylanicum) using disc‐diffusion assay

Abstract: Purpose -This paper is aimed at food science or biology students planning a practical independent study into the antimicrobial properties of spices and academic staff wishing to develop a straightforward and reproducible practical activity. Design/methodology/approach -Disc-diffusion assays are used to investigate the antimicrobial activity of cinnamon and cloves against two bacteria Escherichia coli B and staphylococcus albus and a yeast Saccharomyces cerevisiae. Aqueous and alcoholic extracts of the spices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The result showed essential oil from T. hyemalis inhibited with the range of 19.6 mm to 45 mm. The existence of variations in the inhibition zone can be assumed that due to differences in the number of molecules and chemical type of molecules in the plant materials [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The result showed essential oil from T. hyemalis inhibited with the range of 19.6 mm to 45 mm. The existence of variations in the inhibition zone can be assumed that due to differences in the number of molecules and chemical type of molecules in the plant materials [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study results were better than reported by (Gulay-Kirbasilar et al ., [ 15 ]). This may be due to variations in climate and soil composition in which the plant growing [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro antibacterial activities of T. foenum-graecum extracts were determined by the agar disk diffusion method according to Ghalem and Mohamed (2009). Disk assays were found to be a simple, cheap and reproducible practical method (Maidment et al, 2006). The inocula grown in the nutrient broth at 37ºC for 24 h were diluted to approximately 10 6 CFU/ml in nutrient broth.…”
Section: Agar Disk Diffusion Methodsmentioning
confidence: 99%
“…UPEC isolates were assessed for hemolysis activity on blood agar plates (supplemented with 5% sheep blood), using standard methods (Maidment et al, 2006).…”
Section: Hemolysis Determinationmentioning
confidence: 99%